Popivska Academy Activity in the Beginning of Ethnology Thought on Slobozhanshchyna (the late 18th – early 20th century) - П’ятаченко, Сергій (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
The article deals with the ethnology aspect of cultural and educational group, which operated in the late 18th – early 20th century in Popivka near Sumy led by Oleksander Palitsyn and contributed to the spread of ideas ofenlightenment among the general population and the birth of ethnology thought in Slobozhanshchyna.